2016
DOI: 10.1142/s1464333216500204
|View full text |Cite
|
Sign up to set email alerts
|

Aboriginal Participation in Canadian Environmental Assessment: Gap Analysis and Directions for Scholarly Research

Abstract: There has emerged in recent years an increased industry and regulatory demand for the streamlining of environmental assessment (EA), and at the same time, persistent expectations by Aboriginal communities for more effective and meaningful engagement in development decisions. This paper examines the extent to which scholarly research has contributed to solutions for meaningful Aboriginal participation amidst demands for more efficient and shorter timelines for participation and decision-making. Three research p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…Booth and Skelton (2011a) found that Aboriginal concerns were not taken seriously and there was a lack of respect given to cultural rights. Moreover, inadequacies with regard to the resourcing of Aboriginal participation have been noted in several studies as a procedural component that is vital for EIAs to overcome to be effective (Baker and McLelland 2003;Booth and Skelton 2011b;Udofia et al 2016).…”
Section: Eia and Ex-post Plansmentioning
confidence: 99%
See 1 more Smart Citation
“…Booth and Skelton (2011a) found that Aboriginal concerns were not taken seriously and there was a lack of respect given to cultural rights. Moreover, inadequacies with regard to the resourcing of Aboriginal participation have been noted in several studies as a procedural component that is vital for EIAs to overcome to be effective (Baker and McLelland 2003;Booth and Skelton 2011b;Udofia et al 2016).…”
Section: Eia and Ex-post Plansmentioning
confidence: 99%
“…When done properly with Aboriginal peoples as partners, this may encourage monitoring for learning, understanding and knowledge (Noble 2015;Gallardo et al 2016;Jones and Fischer 2016) and potentially facilitate additional collaborative engagements between parties. Additionally, Udofia et al (2016) identified additional study foci that may be used to form the basis of future collaborations with Aboriginal peoples.…”
Section: Future Considerationsmentioning
confidence: 99%